PENGETAHUAN IBU TENTANG PERAWATAN LUKA PERINEUM PADA IBU POST PARTUM DI RUANGAN NIFAS 3 RSUD ENDE - Raimunda Woga; Maria Salestina Sekunda (Kelimutu Nursing Journal, 2022)
The puerperal period is a dangerous time for the mother, because if not get the proper treatment, then it will threaten the safety of the mother own soul. One of the treatments to be performed is perineal wound care. Therefore, maternal knowledge of perineal wound care is necessary to prevent the occurrence of infections that can threaten the safety of the post-partum mother's life. The purpose of this research is to know the description of the knowledge of postpartum mothers about perineum wound care in Nifas 3 Public Hospital of Ende Area. Type of descriptive research with survey research design. The population of all postpartum mothers treated in NIFAS room 3 in February 2016, amounted to 120 people. The sampling technique is purposive sampling, so the number of samples is 36 people. The results showed that 22 people (61.1%) of post-partum mothers were sufficiently knowledgeable about the meaning and purpose of perineal wound care, and 18 people (50.0%) of post-partum mothers were less knowledgeable about the scope of treatment and time of perineal wound care and 15 people (41,7%) postpartum mothers are knowledgeable about the efforts undertaken in the treatment of perineal wound. The conclusion is that 15 people (41.7%) of postpartum mothers are knowledgeable less about perineal wound care. It is recommended that health workers always provide post-partum health education on care during the puerperium. Nurses/midwives are expected to further improve their skills and always provide friendly service. Friendly service will indirectly help to speed up the recovery process for postpartum mothers.